Evaluation of the Implementation of Internal Control on Cash Sales at CV. Rudang Jaya - Nainggolan, Rahel Junita; Sebayang, Gaby Ibrenna (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the description of the system in the company and evaluate whether the internal control structure for cash sales that has been implemented by the company is adequate and has been implemented effectively. Data collection techniques in this research were carried out using two techniques, namely library techniques obtained through books, previous research, papers, journals and articles. The second technique is a field technique obtained through interview, observation and documentation techniques. Data analysis was carried out by comparing the implementation of internal control over cash sales implemented by the company with existing theories. The results of the research and discussion show that the implementation of internal control over cash sales at CV. Rudang Jaya is good, visible from organizational elements, elements of authorization and recording procedures, as well as elements of healthy practices. Therefore, companies need to supervise the implementation of internal control over cash sales so that the company's existing system can continue to run smoothly..